The emerging 'Alternative' journalism paradigm: Arab journalists and online news. (1st November 2016) - Douai, Aziz; Moussa, Mohamed Ben
The shifting political landscape in the Middle East and North Africa have riveted the world's attention and drawn media scholars' scrutiny to the 'Arab Internet' at large. Despite this attention, research on the 'Arab Internet' has not received its due, and it is even more limited when it comes to exploring online news and journalism. Scholarly works and mainstream media commentary on the subject continue to be predominantly anecdotal with little support from grounded data and evidence. Striving to fill this gap, we argue in this article that the Internet's seeds of the 'Arab Spring' were fomenting for years, slowly but perceptibly transforming Arab news and journalism. To understand these social upheavals requires a dissection of 'online journalism', i.e. the new forms of journalistic practice facilitated by the Web. This article analyses the burgeoning online journalism field in the Arab world, and debates the journalism shifts wrought by the Internet, and the future of journalism practices in the Arab world. We argue that Arab online journalists are constructing a new mode of professional practice, best described as 'alternative' journalism practice.